Measuring intraoperative surgical instrument use with radio-frequency identification. Issue 1 (19th January 2022) - Hill, Ian; Olivere, Lindsey; Helmkamp, Joshua; Le, Elliot; Hill, Westin; Wahlstedt, John; Khoury, Phillip; Gloria, Jared; Richard, Marc J; Rosenberger, Laura H; Codd, Patrick J
Abstract: Objective: Surgical instrument oversupply drives cost, confusion, and workload in the operating room. With an estimated 78%–87% of instruments being unused, many health systems have recognized the need for supply refinement. By manually recording instrument use and tasking surgeons to review instrument trays, previous quality improvement initiatives have achieved an average 52% reduction in supply. While demonstrating the degree of instrument oversupply, previous methods for identifying required instruments are qualitative, expensive, lack scalability and sustainability, and are prone to human error. In this work, we aim to develop and evaluate an automated system for measuring surgical instrument use. Materials and Methods: We present the first system to our knowledge that automates the collection of real-time instrument use data with radio-frequency identification (RFID). Over 15 breast surgeries, 10 carpometacarpal (CMC) arthroplasties, and 4 craniotomies, instrument use was tracked by both a trained observer manually recording instrument use and the RFID system. Results: The average Cohen's Kappa agreement between the system and the observer was 0.81 (near perfect agreement), and the system enabled a supply reduction of 50.8% in breast and orthopedic surgery. Over 10 monitored breast surgeries and 1 CMC arthroplasty with reduced trays, no eliminated instruments were requested, and both trays continue to be used as the supplied standard. Setup time in breast surgery decreased from 23 min to 17 min with the reduced supply. Conclusion: The RFID system presented herein achieves a novel data stream that enables accurate instrument supply optimization. Lay Summary: Surgical instrument oversupply drives cost, confusion, and workload in the operating room. With an estimated 78%–87% of instruments being unused, many health systems have recognized the need for supply refinement. By manually recording instrument use and tasking surgeons to review instrument trays, previous quality improvement initiatives have achieved an average 52% reduction in supply. Despite these successes, methods for identifying required instruments are expensive, qualitative, lack scalability and sustainability, and are prone to human error. In this work, we develop and evaluate an automated radio-frequency identification (RFID) system for measuring surgical instrument use. Over 15 breast surgeries, 10 carpometacarpal (CMC) arthroplasties, and 4 craniotomies, instrument use was tracked by both a trained observer manually recording instrument use and the RFID system. The RFID system achieved near perfect agreement with the observer and enabled an instrument supply reduction of 50.8% in breast and orthopedic surgery. Over 10 monitored breast surgeries and 1 CMC arthroplasty with reduced trays, no eliminated instruments were requested, and both trays continue to be used as the supplied standard. Furthermore, setup time in breast surgery decreased from 23 min to 17 min with the reduced supply.